THE PROBLEM OF THE OPTIMAL PHARMACOTHERAPY CHOICE IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE - S. R. Gilyarevskiy; V. A. Orlov; I. M. Kuz'mina (Столичная издательская компания, 2015)
The problem of the "optimal pharmacotherapy" choice in patients with stable coronary artery disease is discussed. Expert's opinions are presented concerning first-line antiischemic drugs and about current approaches to the choosing additional (adjuvant) antiischemic drugs. The practical application of optimal pharmacotherapy in patients with stable angina pectoris is also discussed.